Self-Reflection and Peer-Assessments Effect on Pharmacy Students' Performance at Simulated Counselling Sessions - Andrew Bartlett; Jessica Pace; Angela Arora; Jonathan Penm (MDPI AG, 2022)
Introduction: Verbal communication is a vital skill for pharmacists and essential for improving patient care. The aim of this study was to explore students' perception of the impact of self-reflection and self- and peer-assessment on simulated patient counselling sessions. Methods: Focus groups explored student perceptions of how this course and way of learning has impacted their performance at counselling patients. Data were analysed using iterative inductive thematic analysis procedures and mapped to the self-determination theory. Results: Nine focus groups with 47 pharmacy students. We identified three main themes and ten associated subthemes. These were learning style (sub-themes gradual introduction to assessment, learning through self-reflection videos, authentic assessment, individual learning compared to group learning, and learning through observation of best practice), feedback (sub-themes inconsistent feedback, summative feedback, perception of self and relationship with peers informing peer assessment) and benefits in real life practice. These themes mapped well to self-determination theory and highlighted that additional focus may be required for benefits in real-life practice. Conclusion: Students' perceptions of self-reflection and self- and peer-assessment centred on learning style, feedback, and benefits in real-life practice. Additional focus on benefits of this unit of study in real-life practice and work integrated learning on placements may further strengthen the impact of these learning activities.